2014
DOI: 10.1186/2251-6581-13-4
|View full text |Cite
|
Sign up to set email alerts
|

Joint effects of mitochondrial DNA 5178 C/A polymorphism and coffee consumption or alcohol consumption on clustering of cardiovascular risk factors in middle-aged Japanese men: a cross-sectional study

Abstract: BackgroundLongevity-associated mitochondrial DNA 5178 (Mt5178) C/A reportedly modulates the effects of coffee consumption on the risk of hypertension, dyslipidemia and abnormal glucose tolerance, and those of alcohol consumption on the risk of hypertension, dyslipidemia and hyperuricemia in middle-aged Japanese men. However, there has been no research examining whether Mt5178 C/A polymorphism influences the effects of coffee consumption or alcohol consumption on the clustering of cardiovascular risk factors (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Previous cross-sectional studies reported the joint effects of Mt5178 C/A polymorphism and coffee consumption on the risk of hypertension [ 16 ], risk of hyper-LDL cholesterolemia [ 17 ] and clustering of cardiovascular risk factors [ 18 ]. Amongst men with Mt5178C genotype, the risk of hypertension was significantly lower in those who consumed ≥2 cups of coffee per day than in those who consumed ≤1 cup of coffee per day [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous cross-sectional studies reported the joint effects of Mt5178 C/A polymorphism and coffee consumption on the risk of hypertension [ 16 ], risk of hyper-LDL cholesterolemia [ 17 ] and clustering of cardiovascular risk factors [ 18 ]. Amongst men with Mt5178C genotype, the risk of hypertension was significantly lower in those who consumed ≥2 cups of coffee per day than in those who consumed ≤1 cup of coffee per day [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Amongst men with Mt5178C genotype, the risk of hypertension was significantly lower in those who consumed ≥2 cups of coffee per day than in those who consumed ≤1 cup of coffee per day [ 16 ]. The risk of the clustering of cardiovascular risk factors was significantly lower in those who consumed ≥1 cup of coffee per day than in those who consumed <1 cup of coffee per day [ 18 ]. Amongst Mt5178A genotypic men, the risk of hyper-LDL cholesterolemia was significantly higher in those who consumed ≥1 cup of coffee per day than in those who consumed <1 cup of coffee per day [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 24 studies were related to cancer ( Table 1 ), [ 17–40 ] and 50 studies to cardiometabolic diseases ( Table 2 ). [ 41–90 ]…”
Section: Methodsmentioning
confidence: 99%